(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to investigate the role of educational institutions in promoting sustainable environmental culture related to solid waste management among school and university students. The study analyzed the level of environmental awareness and examined the role of educational programs and environmental activities in enhancing positive environmental behavior. The study adopted a descriptive-analytical approach, and a questionnaire was used as the primary data collection tool. The sample consisted of 200 students selected randomly and equally distributed between schools and universities. The findings revealed that educational institutions play a significant role in enhancing students’ environmental culture. The overall mean score of environmental awareness ranged from moderate to high. The results also indicated a statistically significant positive relationship between participation in environmental activities and positive environmental behavior among students. Furthermore, environmental educational activities such as recycling campaigns, cleanliness initiatives, and awareness lectures had a direct impact on promoting sustainable environmental behavior. The study also found no major significant differences between school and university students regarding environmental culture, although university students showed slightly higher levels of awareness. In addition, the reliability analysis using Cronbach’s Alpha demonstrated high internal consistency of the research instrument, confirming the reliability of the findings. The study recommends strengthening environmental education programs within educational institutions, enhancing practical environmental activities, and integrating sustainability and solid waste management concepts into educational curricula to build sustainable environmental awareness among students and society.